Impact of Different Stoppers on the Composition of Red and Rosé Lagrein, Schiava (Vernatsch) and Merlot Wines Stored in Bottle - Fabrizio Rossetti; Alicia Jouin; Michael Jourdes; Pierre-Louis Teissedre; Roberta Foligni; Edoardo Longo; Emanuele Boselli (Molecules, 2020)
Different technical cork stoppers (blend of natural cork microgranules, one-piece natural cork, agglomerated natural cork, technical cork 1+1) were compared to evaluate the effects on the phenolic, volatile profiles and dissolved oxygen in three red (Merlot, Lagrein red, St. Magdalener) and one rosé (Lagrein rosé) wines, which were stored in bottles for 12 months. Gallic acid, caffeic acid, p-coumaric acid, trans-resveratrol, glutahionyl caftaric acid and protocatechuic acid did not vary remarkably during the first three months, whereas at six months a net increase was reported, followed by a clear decrease at 12 months. The same trend was observed in Lagrein rosé, but only for gallic acid. The total anthocyanins content decreased during the storage period in the four wines. Isopentyl acetate, 1-hexanol, ethyl hexanoate, 2-phenylethyl alcohol, diethyl succinate, ethyl octanoate and ethyl decanoate were the main volatile compounds. The sum of alcohols decreased in all four of the wines. The esters decreased in Merlot; however, they increased in Lagrein rosé, Lagrein red and St. Magdalener during the storage. Univariate and multivariate statistics and a sensory discriminant triangle test displayed similar influences of the different stoppers on the phenolic and volatile compounds during the whole storage duration. The changes detected in the phenolic and volatile concentrations were presumably due to the non-oxygen-mediated reactions occurring during 12 months of storage in bottle.